THE INFLUENCE OF SUPPLY CHAIN PERFORMANCE AND MOTIVATION ON EMPLOYEE PERFORMANCE - Sutia, Sabar; Riadi, Refren; Fahlevi, Mochammad (International Journal of Supply Chain Management, 2020)
Good performance will support the achievement of supply chain management goals and enhance the competitiveness of the company. There are many factors that affect employee performance improvement, including supply chain management and employee motivation. This study wants to prove the influence of supply chain management and motivation on employee performance. Research conducted at PT. Bank Bukopin with 119 respondents as a sample. There is no influence between motivation on employee performance, simultaneously, there is influence between supply chain management and motivation to employee performance